2008
DOI: 10.1007/s12024-008-9030-3
|View full text |Cite
|
Sign up to set email alerts
|

Histologic dating of bruises in moribund infants and young children

Abstract: It is generally held that leukocytes are found within bruised subcutaneous tissues within 4-12 h of injury as part of a standard cellular response to trauma. As a corollary, the absence of leukocytes is often cited as evidence of more recent injury. To investigate how long after injury it may be before a leukocyte response occurs selected bruises from three children aged 27, 11, and 3 months, respectively, were examined microscopically. All of the children had sustained lethal head trauma, with survival on lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…Moreover, it is impossible to estimate the age of bruises in the absence of an inflammatory reaction. Postmortem examinations of three children with bruises known to be at least 30 hours old revealed in some cases an extravasation of erythrocytes in the subcutis but no infiltration of leucocytes, while other bruises in the children exhibited infiltrating inflammatory cells (Byard and others 2008). An extravasation of erythrocytes in the skin and muscle without an accompanying inflammatory response is therefore not necessarily indicative of a bruise inflicted recently.…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, it is impossible to estimate the age of bruises in the absence of an inflammatory reaction. Postmortem examinations of three children with bruises known to be at least 30 hours old revealed in some cases an extravasation of erythrocytes in the subcutis but no infiltration of leucocytes, while other bruises in the children exhibited infiltrating inflammatory cells (Byard and others 2008). An extravasation of erythrocytes in the skin and muscle without an accompanying inflammatory response is therefore not necessarily indicative of a bruise inflicted recently.…”
Section: Discussionmentioning
confidence: 90%
“…While there has been considerable variation in this proposed orderly sequence, it has been stated that the absence of neutrophils indicates a post-infliction interval of less than 15 h [13]. The demonstration of sections of bruises in three children aged 3, 11, and 27 months who had bruises of at least 24 h duration confirmed by medical evaluation (30, 44, and 79 h before death), with extravasated red blood cells but no leukocyte infiltration or other cellular reaction, however, was not in keeping with this assertion [14]. While this may be due to differences in individual responses to trauma, subsequent studies on human and animal tissues have suggested an additional alternative possibility: i.e.…”
mentioning
confidence: 91%
“…1 Individuals may also have different susceptibility to bruising, with such an idiosyncratic response to injury being shown histologically by a delay in the inflammatory response to bruising in some cases for more than 72 h after an injury. 5 In conclusion, these cases demonstrate that significant and lethal tissue and organ damage can be sustained from blunt trauma with minimal external evidence of injury. The absence of external injury is not, therefore, synonymous with lesser degrees of force, and should not discourage full medicolegal investigation of cases where occult trauma may be a possibility.…”
Section: Discussionmentioning
confidence: 70%